Assessment of neuro-pulmonary crosstalk in asthmatic mice: effects of DiNP exposure on cellular respiration, mitochondrial oxidative status and apoptotic signaling - Kehinde, Samuel Abiodun; Olajide, Abosede Temitope; Ore, Ayokanmi; Praveena, Sarva Mangala; Ataya, Farid S.; El-Gazzar, Ahmed M. (Nature Research, 2024)
Human health is becoming concerned about exposure to endocrine disrupting chemicals (EDCs) emanating from plastic, such as phthalates, which are industrially employed as plasticizers in the manufacturing of plastic products. Due to some toxicity concerns, di(2-ethylhexyl) phthalate (DEHP) was replaced by diisononyl phthalate (DiNP). Recent data, however, highlights the potential of DiNP to interfere with the endocrine system and influence allergic responses. Asthma affects brain function through hypoxia, systemic inflammation, oxidative stress, and sleep disturbances and its effective management is crucial for maintaining respiratory and brain health. Therefore, in DiNP-induced asthmatic mice, this study investigated possible crosstalk between the lungs and the brain inducing perturbations in neural mitochondrial antioxidant status, inflammation biomarkers, energy metabolizing enzymes, and apoptotic indicators. To achieve this, twelve (n = 12, 20–30 g) male BALB/c mice were divided into two (2) experimental groups, each with five (6) mice. Mice in group II were subjected to 50 mg/kg body weight (BW) DiNP (Intraperitoneal and intranasal), while group I served as the control group for 24 days. The effects of DiNP on neural energy metabolizing enzymes (Hexokinase, Aldolase, NADase, Lactate dehydrogenase, Complex I, II, II & IV), biomarkers of inflammation (Nitric oxide, Myeloperoxidase), oxidative stress (malondialdehyde), antioxidants (catalase, glutathione-S-transferase, and reduced glutathione), oncogenic and apoptotic factors (p53, K-ras, Bcl, etc.), and brain histopathology were investigated. DiNP-induced asthmatic mice have significantly (p < 0.05) altered neural energy metabolizing capacities due to disruption of activities of enzymes of glycolytic and oxidative phosphorylation. Other responses include significant inflammation, oxidative distress, decreased antioxidant status, altered oncogenic-apoptotic factors level and neural degeneration (as shown in hematoxylin and eosin-stained brain sections) relative to control. Current findings suggest that neural histoarchitecture, energy metabolizing potentials, inflammation, oncogenic and apoptotic factors, and mitochondrial antioxidant status may be impaired and altered in DiNP-induced asthmatic mice suggesting a pivotal crosstalk between the two intricate organs (lungs and brain).